Penerapan Model Pembelajaran PBL Untuk Mengembangkan Kemampuan Pemecahan Masalah Matematika - Sujana, Asep (Pasundan Journal of Mathematics Education : Jurnal Pendidikan Matematika, 2020)
This research is a mixed method research with concurrent embedded strategy. The aim of the research is to find outthe students’ ability in mathematical problem solving that learn with problem-based learning (PBL) is better than the conventional learning; The population of the researchwas the mathematics education students of FKIP UNMA Banten.The sample of the research was two classes in semester IV. The instrumentsin this research werean essay, questionnaires and observation sheet of students’ and lecturersactivities. The data were analyzed quantitatively and qualitatively that was obtained from the pretest and posttest. The results showed thatthere is no significant difference between the students’ ability in mathematical problem solving that learnt with the problem-based learning (PBL) and the conventional learning.